Preparation method of multi-gradient pore structure carbon fiber paper for gas diffusion layer of fuel cell and carbon fiber paper

By adopting carbon fiber paper with a multi-gradient pore structure in the fuel cell gas diffusion layer, the problem of insufficient water management capabilities in the existing technology is solved, more efficient water and gas management is achieved, and the performance of fuel cells is improved.

CN119754079APending Publication Date: 2025-04-04TIANJIN UNIV OF SCI & TECH

Patent Information

Application Number
CN202411989104.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The water management capabilities of existing fuel cell gas diffusion layers are difficult to adapt to under strict environmental conditions such as full humidity and high current density, resulting in water flooding and electrode performance degradation.

Method used

Carbon fiber paper with multi-gradient pore structure is adopted to regulate the pore structure of carbon fiber raw paper through mechanical treatment and the addition of nanofibers, and low, medium and high pore-size gradient carbon fiber paper is constructed. Combined with carbonization and graphitization treatment, the conductivity and gradient of pore structure of carbon fiber paper are improved.

Benefits of technology

It significantly improves the water and gas management capabilities of fuel cells, enhances water removal capabilities, reduces contact resistance, and improves gas delivery efficiency, thereby improving the performance of fuel cells under strict conditions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of fuel cells, in particular to a preparation method of multi-gradient pore structure carbon fiber paper for a gas diffusion layer of a fuel cell and the carbon fiber paper. The preparation method comprises the following steps: carrying out mechanical treatment on artificial fibers, and carrying out solid-liquid separation to obtain mechanically treated artificial fiber slurry; mixing the fiber slurry with nanofibers and surface modified carbon fibers to prepare composite fiber slurry; an inclined wire wet forming process is adopted, the pore structures of the carbon fiber base paper are regulated and controlled by adjusting the proportion of fibers with different sizes, and the carbon fiber base paper with different pore structures is subjected to multi-layer compounding according to a certain gradient of low, medium and high; after compounding, the carbon fiber paper with a multi-gradient pore structure is prepared through the processes of resin impregnation, hot-pressing curing, carbonization, graphitization and the like. The preparation method provided by the invention is simple and convenient in process flow, meets the requirements of high conductivity, high air permeability and high strength of the carbon fiber paper, optimizes the drainage capacity of the battery, and improves the battery performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fuel cells, and in particular to a method for preparing a carbon fiber paper with a multi-gradient pore structure for a gas diffusion layer of a fuel cell and the carbon fiber paper. Background Art

[0002] Fuel cell power generation technology is considered to be the preferred clean and efficient power generation technology in the 21st century. As the best way to efficiently and cleanly utilize hydrogen energy, its main principle is to use an energy conversion device that directly converts chemical energy into electrical energy through electrochemical reactions. The reaction process is not limited by the Carnot cycle, has a fast startup speed, and a high energy conversion rate. Among many fuel cells, proton exchange membrane fuel cells are considered to be the most promising type of fuel cell in the field of future energy conversion technology. The gas diffusion layer, a key component of proton exchange membrane fuel cells, has the functions of supporting the catalyst layer, stabilizing the electrode structure, providing channels for fuel diffusion, electron conduction, and eliminating water generated by the battery, which directly affects the battery performance. Carbon paper is the key supporting material for the gas diffusion layer. Its pore structure, porosity, and conductivity determine the material transport performance of the substrate layer.

[0003] The degree of hydration of the proton exchange membrane of a fuel cell determines its performance and durability. The water content of the membrane corresponding to the inlet end is relatively low, and the gas diffusion layer needs to have good hydrophilicity to maintain the water required for high-performance reactions. The water content of the membrane at the exhaust end is relatively high, and there is more water accumulation in the flow field and diffusion layer, so it is necessary to have good hydrophobicity to drain the water produced by the catalyst layer in time to avoid flooding. Therefore, a base layer of carbon fiber paper with a gradient pore size distribution is constructed, and a small-pore carbon paper is placed on the side close to the catalyst layer, and a large-pore carbon paper is placed on the side close to the bipolar plate to ensure that the pore size between the base layer and the microporous layer in the gas diffusion layer changes from the initial mutation state to a smooth transition state. The resulting capillary pressure difference can effectively enhance the transmission of water, balance the distribution of water in the gas diffusion layer, strengthen the water management ability of the fuel cell, and thus improve the performance of the fuel cell under strict conditions.

[0004] Chinese patent CN110890555B prepares a gradient microporous layer on the surface of carbon paper, and adds additional auxiliary additives to extend the life of the fuel cell, thereby improving the hydrophilic and hydrophobic management of different areas of the fuel cell, thereby improving the performance and reliability of the fuel cell. However, the small pore size of the microporous layer has limited improvement in water management capabilities, and the carbon fiber paper prepared without carbonization and graphitization has poor conductivity. Chinese patent CN115425239A provides a method for preparing a microporous layer with a double gradient of hydrophobicity and air permeability. By preparing two slurries containing different doses of hydrophobic agents and adding pore-forming agents, a gradient structure with decreasing hydrophobicity is obtained, thereby improving the water management and gas transmission capabilities of the gas diffusion layer. However, the pore size gradient span formed between the microporous layer and the macroporous matrix is ​​too large. When the water in the microporous layer diffuses into the macroporous matrix layer, the water will still gather and stay there, causing electrode flooding and hindering the mass transfer of fuel gas and water.

[0005] Although the pore gradient design of the microporous layer in the gas diffusion layer can improve the water management ability and battery performance of the PEM fuel cell, it is still difficult to adapt to more stringent environmental conditions such as full humidity and high current density. This is because the microporous layer accounts for a relatively low proportion of the entire GDL, and the improvement in the water management ability of the fuel cell is limited. For the water management of PEM fuel cells, when water is discharged from the catalyst layer, most of the water will pass through the thicker and more porous GDL substrate layer. Therefore, the GDL substrate layer plays a decisive role in the water management of the fuel cell. Constructing a substrate layer with a gradient pore structure has a higher capillary pressure difference, which can effectively improve the transmission of water, balance the distribution of water in the GDL, and strengthen the water management ability of the fuel cell, thereby improving the performance of the fuel cell under strict conditions. Summary of the invention

[0006] The main purpose of the present invention is to overcome the shortcomings and defects mentioned in the above background technology, and provide a method for preparing a multi-gradient pore structure carbon fiber paper for a fuel cell gas diffusion layer and a carbon fiber paper, comprising the following steps:

[0007] Mechanically treating the man-made fiber and performing solid-liquid separation to obtain mechanically treated man-made fiber slurry;

[0008] The mechanically treated fiber slurry, nanofibers and surface-modified carbon fibers are mixed to obtain composite fiber slurry, and wet-formed to obtain carbon fiber base papers with different quantifications and different pore structures, and the carbon fiber base papers with different pore structures are multi-layered according to a certain gradient of low, medium and high pores to obtain composite carbon fiber paper base paper; or multi-layer composite net wet-formation technology is used to directly stack multiple layers online to obtain composite carbon fiber paper base paper;

[0009] The composite carbon fiber paper base paper is immersed in a resin solution for a period of time, taken out and dried, and then hot-pressed and cured to obtain a carbon fiber / resin composite, and the carbon fiber / resin composite is sequentially carbonized and graphitized;

[0010] The prepared carbon paper is assembled into a single cell, with small-pore carbon paper placed close to the catalyst layer and large-pore carbon paper placed close to the bipolar plate, and the fuel cell performance is assembled and tested.

[0011] Preferably, the types of man-made fibers include regenerated cellulose fibers such as viscose fibers and lyocell fibers, the mechanical treatment is pulping / refining treatment, the pulping revolutions are 3000-20000r, the beating degree of the man-made fiber slurry is 10-80°SR, and the amount of man-made fibers used is 1-20% of the carbon fiber paper base.

[0012] Preferably, the nanofibers include but are not limited to one or more of nanocellulose, aramid nanofibers, and carbon nanofibers, with a fiber diameter of 20-1000 nm and an aspect ratio of 20-700. The amount of the nanofibers used is 0.5-10% of the carbon fiber paper base.

[0013] Preferably, the carbon fiber is one or more of polyacrylonitrile carbon fiber, asphalt-based carbon fiber, and rayon carbon fiber, the length of the carbon fiber is 3-6 mm, and the concentration of the fiber / carbon fiber mixed slurry is 0.02-0.5%.

[0014] Preferably, the number of composite layers of the carbon fiber paper is 2-5, and composite carbon fiber paper with low, medium and high pore size gradients is prepared, wherein the minimum pore size in the multi-layer paper with low pore gradient is 6-12 μm and the maximum pore size is 8-14 μm; the minimum pore size in the multi-layer paper with medium pore gradient is 3-8 μm and the maximum pore size is 10-20 μm; the minimum pore size in the multi-layer paper with high pore gradient is 1-5 μm and the maximum pore size is 18-26 μm.

[0015] Preferably, the wet forming process uses a single-layer or multi-layer composite web forming process, and the composite web includes one or more of a long web, an oblique web, a round web or a stacked web.

[0016] Preferably, the impregnation resin solution is a phenolic resin-ethanol solution, the concentration of the phenolic resin is 5-30%, and the impregnation time is 0.5-2h.

[0017] Preferably, the temperature of hot pressing curing is 120-250° C., the pressure is 2-20 MPa, and the time is 10-60 min.

[0018] Preferably, the carbonization temperature is 1200-1600° C., the graphitization temperature is 2400-3200° C., and the pressure applied to the paper during the carbonization and graphitization process is 1-100 kPa.

[0019] The present invention also provides carbon fiber paper prepared by the above preparation method, wherein the gas permeability of the carbon fiber paper is preferably 1500-2400 ml·mm / (cm 2 ·hr·mmAq), the plane resistivity is preferably 15-25mΩ·cm, the vertical resistivity is preferably 80-120mΩ·cm, and the tensile strength is preferably 18-25MPa.

[0020] Compared with the prior art, the present invention has achieved the following technical effects:

[0021] (1) By adding different proportions of nanofibers, man-made fibers and carbon fibers, the pore structure of carbon fiber base paper can be effectively regulated. The hydrophilic groups on the surface of man-made fibers and nanofibers and the oxygen-containing groups on the surface of carbon fibers form a large number of hydrogen bonds between the fibers. At the same time, the fiber swelling reduces the pore size, and the fine fiber components fill the pores of the carbon paper to adjust the pore structure.

[0022] (2) Gradient treatment of the substrate layer. The pore structure is optimized and reconstructed by multi-layer composite of carbon fiber paper to construct a carbon fiber paper with a low, medium and high gradient distribution of pore size in the vertical direction. This gradient provides an additional driving force for drainage, improves the water removal capacity of the fuel cell, promotes high current density drainage and low current density water retention. It reduces contact resistance, improves gas transport efficiency, and significantly improves the water and gas management capabilities of proton exchange membrane fuel cells, thereby improving the battery performance of fuel cells under strict conditions. DETAILED DESCRIPTION

[0023] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0024] Example 1

[0025] 20 g of absolutely dry Lyocell fiber (length 6 mm) was added with deionized water to make 200 g, and the mixture was mixed and beaten in a PFI machine at a beating speed of 8000 r and a beating degree of 38° SR to obtain a beating-treated Lyocell fiber slurry;

[0026] The above-mentioned Lyocell fiber slurry treated with pulping and the surface-modified carbon fiber were mixed in an absolute dry weight ratio of 1:9, 2:8, and 3:7 to construct a low-gradient carbon fiber base paper, deionized water was added to the slurry, and a composite fiber slurry was obtained after being treated with a deflaker. The slurry concentration was 0.1%. The inclined mesh wet forming process was adopted, and three carbon fiber paper base papers were obtained by dehydration, pressing, drying, etc., with pore sizes of 7 μm, 10 μm, and 13 μm, respectively;

[0027] Three carbon fiber paper base papers were immersed in a phenolic resin-ethanol solution with a concentration of 12% for 1 hour, laminated and dried according to the pore size distribution from large to small, and hot-pressed and cured with a flat vulcanizer at 140°C and 4MPa to obtain a carbon fiber / resin composite.

[0028] The carbon fiber / resin composite was carbonized-graphitized under certain pressure, the carbonization temperature was 1600°C, the graphitization temperature was 3000°C, and the pressure applied to the paper during the carbonization and graphitization process was 50kPa, and finally carbon fiber paper was produced.

[0029] The performance parameters of the prepared carbon fiber paper are: thickness of 276 μm, gas permeability of 2100 ml·mm / (cm 2 ·hr·mmAq), porosity is 80%, plane resistivity is 15mΩ·cm, vertical resistivity is 80mΩ·cm, tensile strength is 20MPa, and stiffness is 342mN (angle 15°, length 10mm).

[0030] Example 2

[0031] 20 g of absolutely dry Lyocell fiber (length 6 mm) was added with deionized water to make 200 g, and the mixture was mixed and beaten in a PFI machine at a beating speed of 8000 r and a beating degree of 38° SR to obtain a beating-treated Lyocell fiber slurry;

[0032] The above-mentioned Lyocell fiber slurry treated with pulping and the surface-modified carbon fiber were mixed in an absolute dry weight ratio of 1:9, 3:7, and 5:5 to construct a medium-gradient carbon fiber base paper, deionized water was added to the slurry, and a composite fiber slurry was obtained after being treated with a deflaker. The slurry concentration was 0.1%. The inclined mesh wet forming process was adopted, and the carbon fiber paper base paper was obtained by dehydration, pressing, drying and other processes, and the pore sizes were 7 μm, 13 μm, and 19 μm, respectively;

[0033] Three carbon fiber paper base papers were immersed in a phenolic resin-ethanol solution with a concentration of 12% for 1 hour, laminated and dried according to the pore size distribution from large to small, and hot-pressed and cured with a flat vulcanizer at 140°C and 4MPa to obtain a carbon fiber / resin composite.

[0034] The carbon fiber / resin composite was carbonized-graphitized under certain pressure, the carbonization temperature was 1600°C, the graphitization temperature was 3000°C, and the pressure applied to the paper during the carbonization and graphitization process was 50kPa, and finally carbon fiber paper was produced.

[0035] The performance parameters of the prepared carbon fiber paper are: thickness of 254 μm, gas permeability of 2000 ml·mm / (cm 2 ·hr·mmAq), porosity is 65%, plane resistivity is 16mΩ·cm, vertical resistivity is 98mΩ·cm, tensile strength is 22MPa, and stiffness is 363mN (angle 15°, length 10mm).

[0036] Example 3

[0037] 20 g of absolutely dry Lyocell fiber (length 6 mm) was added with deionized water to make 200 g, and the mixture was mixed and beaten in a PFI machine at a beating speed of 8000 r and a beating degree of 38° SR to obtain a beating-treated Lyocell fiber slurry;

[0038] The above-mentioned Lyocell fiber slurry treated with pulping and the surface-modified carbon fiber were mixed in an absolute dry weight ratio of 1:9, 4:6, and 7:3 to construct a high-gradient carbon fiber base paper, deionized water was added to the slurry, and the composite fiber slurry was obtained after being treated with a deflaker. The concentration of the slurry was 0.1%. The inclined mesh wet forming process was adopted, and the carbon fiber paper base paper was obtained by dehydration, pressing, drying and other processes, and the pore sizes were 7 μm, 16 μm, and 25 μm, respectively;

[0039] Three carbon fiber paper base papers were respectively immersed in a phenolic resin-ethanol solution with a concentration of 12% for 1 hour, and then laminated and dried according to the pore size distribution from large to small. The carbon fiber / resin composite was obtained by hot pressing and curing with a flat vulcanizer at 140°C and 4MPa.

[0040] The carbon fiber / resin composite was carbonized-graphitized under certain pressure, the carbonization temperature was 1600°C, the graphitization temperature was 3000°C, and the pressure applied to the paper during the carbonization and graphitization process was 50kPa, and finally carbon fiber paper was produced.

[0041] The performance parameters of the prepared carbon fiber paper are: thickness of 268 μm, gas permeability of 2100 ml·mm / (cm 2 ·hr·mmAq), porosity is 83%, plane resistivity is 18mΩ·cm, vertical resistivity is 87mΩ·cm, tensile strength is 21MPa, and stiffness is 314mN (angle 15°, length 10mm).

[0042] Example 4

[0043] 10 g of absolutely dry Lyocell fiber (length 6 mm) was added with deionized water to make 200 g, and the mixture was mixed and beaten in a PFI machine at a beating speed of 8000 r and a beating degree of 38° SR to obtain a beating-treated Lyocell fiber slurry;

[0044] The above-mentioned Lyocell fiber slurry treated by pulping, 100g of CNF with a concentration of 10%, and surface-modified carbon fiber are mixed in an absolute dry mass ratio of 1:1:8, 2:2:6, and 3:3:4 to construct a gradient carbon fiber base paper, deionized water is added to the slurry, and a composite fiber slurry is obtained after being treated with a deflaker. The slurry concentration is 0.1%. The inclined mesh wet forming process is adopted, and the carbon fiber paper base paper is obtained by dehydration, pressing, drying and other processes, and the pore sizes are 8μm, 14μm, and 20μm, respectively;

[0045] Three carbon fiber paper base papers were immersed in a phenolic resin-ethanol solution with a concentration of 12% for 1 hour, laminated and dried according to the pore size distribution from large to small, and hot-pressed and cured with a flat vulcanizer at 140°C and 4MPa to obtain a carbon fiber / resin composite.

[0046] The carbon fiber / resin composite was carbonized-graphitized under certain pressure, the carbonization temperature was 1600°C, the graphitization temperature was 3000°C, and the pressure applied to the paper during the carbonization and graphitization process was 50kPa, and finally carbon fiber paper was produced.

[0047] The performance parameters of the prepared carbon fiber paper are: thickness 247μm, gas permeability 1892ml·mm / (cm 2 ·hr·mmAq), porosity is 68%, plane resistivity is 17mΩ·cm, vertical resistivity is 101mΩ·cm, tensile strength is 23MPa, and stiffness is 353mN (angle 15°, length 10mm).

[0048] Comparative Example 1

[0049] 20 g of absolutely dry Lyocell fiber (length 6 mm) was added with deionized water to make 200 g, and the mixture was mixed and beaten in a PFI machine at a beating speed of 8000 r and a beating degree of 38° SR to obtain a beating-treated Lyocell fiber slurry;

[0050] The Lyocell fiber slurry treated with the above pulping and the surface-modified carbon fiber were mixed in an absolute dry weight ratio of 1:9 and 2:8, deionized water was added to the slurry, and a composite fiber slurry was obtained after being treated with a deflaker. The slurry concentration was 0.1%. The inclined net wet forming process was adopted, and two carbon fiber paper base papers were obtained through dehydration, pressing, drying and other processes, and the pore sizes were 7 μm and 10 μm respectively.

[0051] Two sheets of carbon fiber paper were immersed in a phenolic resin-ethanol solution with a concentration of 12% for 1 hour, laminated and dried according to the pore size distribution from large to small, and hot-pressed and cured with a flat vulcanizer at 140°C and 4MPa to obtain a carbon fiber / resin composite.

[0052] The carbon fiber / resin composite was carbonized-graphitized under certain pressure, the carbonization temperature was 1600°C, the graphitization temperature was 3000°C, and the pressure applied to the paper during the carbonization and graphitization process was 50kPa, and finally carbon fiber paper was produced.

[0053] The performance parameters of the prepared carbon fiber paper are: thickness 156μm, gas permeability 2230ml·mm / (cm 2 ·hr·mmAq), porosity is 80%, plane resistivity is 15mΩ·cm, vertical resistivity is 80mΩ·cm, tensile strength is 19MPa, and stiffness is 342mN (angle 15°, length 10mm).

[0054] Comparative Example 2

[0055] 20 g of absolutely dry Lyocell fiber (length 6 mm) was added with deionized water to make 200 g, and the mixture was mixed and beaten in a PFI machine at a beating speed of 8000 r and a beating degree of 38° SR to obtain a beating-treated Lyocell fiber slurry;

[0056] The above-mentioned Lyocell fiber slurry treated with pulping and the surface-modified carbon fiber were mixed at an absolute dry weight ratio of 3:7, deionized water was added to the slurry, and a composite fiber slurry was obtained after being treated with a deflaker. The slurry concentration was 0.1%. The inclined net wet forming process was adopted, and three carbon fiber paper base papers were obtained through dehydration, pressing, drying and other processes, and the pore size was 13 μm.

[0057] Three sheets of carbon fiber paper were impregnated in a phenolic resin-ethanol solution with a concentration of 12% for 1 hour, laminated and dried according to the pore size distribution from large to small, and hot-pressed and cured with a flat vulcanizer at 140°C and 4MPa to obtain a carbon fiber / resin composite.

[0058] The carbon fiber / resin composite was carbonized-graphitized under certain pressure, the carbonization temperature was 1600°C, the graphitization temperature was 3000°C, and the pressure applied to the paper during the carbonization and graphitization process was 50kPa, and finally carbon fiber paper was produced.

[0059] The performance parameters of the prepared carbon fiber paper are: thickness of 264 μm, gas permeability of 1800 ml·mm / (cm 2 ·hr·mmAq), porosity is 74%, plane resistivity is 17mΩ·cm, vertical resistivity is 92mΩ·cm, tensile strength is 22MPa, and stiffness is 269mN (angle 15°, length 10mm).

[0060] Comparative Example 3

[0061] The preparation method is the same as that of Example 1, except that: the carbon fibers are mixed in a ratio of 4:6 by absolute dry weight to prepare three carbon fiber base papers with a pore size of 16 μm;

[0062] The performance parameters of the prepared carbon fiber paper are: thickness 272μm, gas permeability 1730ml·mm / (cm 2 ·hr·mmAq), porosity is 73%, plane resistivity is 25mΩ·cm, vertical resistivity is 116mΩ·cm, tensile strength is 23MPa, and stiffness is 214mN (angle 15°, length 10mm).

[0063] Membrane electrode performance test

[0064] The gas diffusion layers prepared in the above examples and comparative examples were cut into pieces of 5x5 cm 2 The size of the battery was assembled into a single cell, and the polarization curve and power density curve of the single cell were tested. The electrochemical performance test of the single cell was carried out at a cathode-cathode ratio of 2:4, an anode back pressure of 140KPa, a cathode back pressure of 120KPa, a relative humidity of 100%, and a battery temperature of 80°C.

[0065] The maximum power densities of the membrane electrodes prepared by the gas diffusion layers of Example 1 and Comparative Example 1 were 0.93 and 0.81 W / cm -2 When the current density is greater than 1.0Acm -2 When entering the mass transfer polarization region, the gas diffusion layer mass transfer efficiency of Example 1 is higher than that of Comparative Example 1. This shows that the three-layer carbon paper has a better gradient pore structure, and the reaction gas and the generated water can transfer substances in more pore channels. Under 100% humidity conditions, not only the discharge of liquid water is accelerated, but also additional humidification is obtained during the diffusion of oxygen from the outside to the catalyst layer, which improves the working performance of the membrane electrode and ensures the stable progress of the reaction.

[0066] The performance of the gas diffusion layer with mesoporous gradient in Example 2 was average, with a current density of 1.8 A / cm 2 The maximum output power is 0.98W / cm 2 The high porosity gradient gas diffusion layer of Example 3 can adapt to 100% humidity environment, and the current density can reach up to 2.1A / cm 2 , its maximum output power is 1.24W / cm 2 The results show that the membrane electrode prepared by the gas diffusion layer of Example 3 has the best performance, good pore structure and air permeability, improved water distribution and gas transmission, and the reactants are replenished in time; the proton exchange membrane has a high degree of hydration, which reduces the mass transfer polarization and improves the power generation efficiency of the fuel cell. The maximum output power of Example 4 is 1.03W / cm 2 The hydrogen bonds between Lyocell fibers and CNF fibers increase the strength of carbon paper, and the fine fiber components fill the pores of carbon paper to adjust the pore size structure. However, the battery performance is still inferior to that of Example 3. The maximum output power of Comparative Examples 2 and 3 is 0.74 W / cm 2 、0.78W / cm 2 The gradient pore size distribution of the carbon fiber paper produced does not change significantly, the capillary pressure is low, and compared with the multi-gradient pore structure, the drainage effect is not ideal and flooding is prone to occur.

[0067] The present invention uses specific examples to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea; at the same time, these modifications or improvements made without departing from the present invention are all within the scope of protection required by the present invention.

Claims

1. A method for preparing a carbon fiber paper with a multi-gradient pore structure for a fuel cell gas diffusion layer, characterized in that: The following steps are involved: Mechanically treating the man-made fiber and performing solid-liquid separation to obtain mechanically treated man-made fiber slurry; The mechanically treated fiber slurry, nanofibers and surface-modified carbon fibers are mixed to obtain composite fiber slurry, and wet-formed to obtain carbon fiber base papers with different quantifications and different pore structures, and the carbon fiber base papers with different pore structures are multi-layered according to a certain gradient of low, medium and high pores to obtain composite carbon fiber paper base paper; or multi-layer composite net wet-formation technology is used to directly stack multiple layers online to obtain composite carbon fiber paper base paper; The composite carbon fiber paper base paper is immersed in a resin solution for a period of time, taken out and dried, and then hot-pressed and cured to obtain a carbon fiber / resin composite, and the carbon fiber / resin composite is sequentially carbonized and graphitized; The prepared carbon paper is assembled into a single cell, with small-pore carbon paper placed close to the catalyst layer and large-pore carbon paper placed close to the bipolar plate, and the fuel cell performance is assembled and tested.

2. The method for preparing the multi-gradient pore structure carbon fiber paper for the fuel cell gas diffusion layer according to claim 1, characterized in that: The types of artificial fibers include viscose fibers, lyocell fibers and other regenerated cellulose fibers. The mechanical treatment is pulping / refining treatment. The pulping revolutions are 3000-50000r. The beating degree of the artificial fiber pulp is 10-80°SR. The amount of artificial fibers used is 1-20% of the carbon fiber paper base.

3. The preparation method according to claim 1, characterized in that: The nanofibers include but are not limited to one or more of nanocellulose, aramid nanofibers, and carbon nanofibers. The fiber diameter is 20-1000 nm, the aspect ratio is 20-700, and the amount of the nanofibers is 0.5-10% of the carbon fiber paper.

4. The preparation method according to claim 1, characterized in that: The carbon fiber is one or more of polyacrylonitrile carbon fiber, asphalt-based carbon fiber and rayon carbon fiber. The length of the carbon fiber is 1-10 mm. The concentration of the fiber / carbon fiber mixed slurry is 0.02-0.5%.

5. The preparation method according to claim 1, characterized in that: The number of composite layers of carbon fiber paper is 2-5, and composite carbon fiber paper with low, medium and high pore size gradients is prepared, wherein the minimum pore size in the multi-layer paper with low pore gradient is 6-12μm and the maximum pore size is 8-14μm; the minimum pore size in the multi-layer paper with medium pore gradient is 3-8μm and the maximum pore size is 10-20μm; the minimum pore size in the multi-layer paper with high pore gradient is 1-5μm and the maximum pore size is 18-26μm.

6. The preparation method according to claim 1, characterized in that: The wet forming process uses a single-layer or multi-layer composite mesh forming process, and the composite mesh includes one or more of a long mesh, an oblique mesh, a round mesh or a stacked mesh forming method.

7. The preparation method according to claim 1, characterized in that: The impregnation resin solution is a phenolic resin-ethanol solution, the concentration of the phenolic resin is 5-40%, the impregnation time is 0.5-3h, the temperature of hot pressing curing is 120-250°C, the pressure is 2-30MPa, and the time is 10-60min.

8. The preparation method according to claim 1, characterized in that: The carbonization temperature is 1200-1600°C, the graphitization temperature is 2400-3200°C, and the pressure applied to the paper during the carbonization and graphitization process is 1-100 kPa.

9. The carbon fiber paper prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The gas permeability of the carbon fiber paper is 1400-2400 ml·mm / (cm 2 ·hr·mmAq), plane resistivity is 10-30mΩ·cm, vertical resistivity is 80-130mΩ·cm, and tensile strength is 17-25MPa.

Citation Information

Patent Citations

  • A method for preparing a gradient hydrophilic or hydrophobic diffusion layer

    CN110890555B

  • Preparation method of microporous layer with double gradients of hydrophobicity and air permeability

    CN115425239A

  • Preparation method of carbon paper precursor for gas diffusion layer of fuel cell

    CN111900418A

  • Preparation method of gradient pore structure carbon paper

    CN113322713A

  • Carbon fiber paper for gas diffusion layer of fuel cell as well as preparation method and application of carbon fiber paper

    CN115341407A

Cited By

  • Gradient pore carbon paper base material based on gum dipping-doping cooperative regulation and preparation method

    CN121097098A

  • Pore-adjustable carbon fiber paper for supercapacitor electrode and preparation method of pore-adjustable carbon fiber paper

    CN121439531A